THE ROLE OF THE PUJAKESUMA ASSOCIATION IN WINNING SIMALUNGUN REGENCY LEGISLATIVE CANDIDATES IN THE 2024 ELECTION: PERAN PAGUYUBAN PUJAKESUMA DALAM PEMENANGAN CALON LEGISLATIF KABUPATEN SIMALUNGUN PADA PEMILU 2024 - Najwa El-Khoir Hasibuan; Elly Warnisyah Harahap (SOSIOEDUKASI, 2025)
This article discusses how the role given by the Pujakesuma group, especially in winning legislative candidates in Simalungun Regency, which is a minority area of the Javanese tribe, in the 2024 election. The writing of this journal uses a qualitative method, with data collection techniques in the form of in-depth interviews with figures from the Pujakesuma community, which is accompanied by documentation and literature studies. The analysis technique used is a qualitative descriptive analysis, through references from journals, and books that are then re-analyzed by the author. The findings obtained from this study are that the largest votes obtained from ethnic Javanese were obtained in Bandar Masalam district, which is an area with a majority of ethnic Javanese ethnicity. The Pujakesuma Association played a major role in winning legislative candidates in Simalungun Regency in the 2024 election.  This shows that associations that are synonymous with cultural organizations can take an important role in politics. A well-managed cultural realm will create good results in the surrounding environment, including in the political environment.